Investment Risks and Insurance in the Gold Market - Megits, Nikolay; Reverchuk, Serhij; Chyzh, Lyudmyla (Journal of Eastern European and Central Asian Research (JEECAR), 2014)
<!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> In this article we investigated the causes and features of investment risks in the gold market, studied the components of investment risks in this market, and analyzed the main methods of insuring those investment risks. In addition, we presented the methods and financial investment instruments used in gold operations and provided the conceptual analyses of investment risk in the gold market. <!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0pt 5.4pt 0pt 5.4pt; mso-para-margin:0pt; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –> <!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> <!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> <!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0pt 5.4pt 0pt 5.4pt; mso-para-margin:0pt; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>